Internal conflicts of a person in the spiritually-semantic paradigm - Красильников, Ігор Олександрович (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2017)
In the article the analysis of theoretical positions of existential-semantic psychology of V. Frankl in a context of internal conflicts of the person is presented. It is emphasized, that the semantic phenomenon of the person underlies in internal conflicts of the person. The existential phenomenology, as the methodological approach to understanding of subject-spiritual abilities on overcoming an internal conflictness is considered